2014
DOI: 10.1007/s10517-014-2699-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Gelatin Concentrations in Silk Fibroin-Based Composite Scaffolds and Adhesion and Proliferation of Mouse Embryo Fibroblasts

Abstract: Porous scaffolds of silk fibroin and composite porous scaffolds with 10, 20, 30, 40, and 50% gelatin were made by the freezing-thawing method. The relationship between adhesion and proliferation rate mouse embryo fibroblast and the scaffold composition was studied by laser confocal scanning microscopy. Addition of gelatin to the scaffold structure stimulated adhesion and proliferation of mouse embryo fibroblasts; the optimal content of gelatin was 30%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…To answer these questions, we have evaluated two types of previously described silk-based MPs, generated from fibroin/gelatin (20, 21) scaffolds or spidroin (2224) hydrogels and characterized their regenerative and inflammatory potential in vivo in the model of murine deep skin wounds, as well as direct effects on inflammatory and profibrotic genes expression in several cell types involved in skin regeneration in vitro . We have demonstrated that, while possessing similar proregenerative potential, these vehicles are remarkably different in their interaction with the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…To answer these questions, we have evaluated two types of previously described silk-based MPs, generated from fibroin/gelatin (20, 21) scaffolds or spidroin (2224) hydrogels and characterized their regenerative and inflammatory potential in vivo in the model of murine deep skin wounds, as well as direct effects on inflammatory and profibrotic genes expression in several cell types involved in skin regeneration in vitro . We have demonstrated that, while possessing similar proregenerative potential, these vehicles are remarkably different in their interaction with the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Клеточные линии и условия культивирования. Выделение мышиных эмбриональных фибробластов (МЭФ), экспрессирующих зеленый флуоресцентный белок (GFP, green fluorescent protein), проводили, как описано ранее [9]. МЭФ и иммортализованные мышиные фибробласты линии 3Т3 культивировали в среде Игла в модификации Дульбекко (DMEM) производства ПанЭко (Россия), содержащей 10% эмбриональной телячьей сыворотки (ЭТС) производства HyClone (США).…”
Section: материалы и методыunclassified
“…Матриксы из фиброина и композитные матриксы на основе фиброина с 30% содержанием желатина получали по методике, описанной ранее [6]. Из матриксов путем криоизмельчения полу-чены МН -соответственно на основе фиброина (Ф-МН) и на ос-нове композитного материала, содержащего фиброин и 30% жела-тина (ФЖ-МН).…”
Section: материалы и методыunclassified
“…При этом в другой работе нами показано, что введе-ние желатина в состав макроносителей на основе фиброи-на в виде трехмерных пористых матриксов, таких как представлены на рис. 1, а, б, приводило к усилению про-лиферативной активности ФБ линии клеток 3Т3 [6].…”
Section: рис 2 культивирование мышиных фб линии 3т3 на мн двух типовunclassified
See 1 more Smart Citation